الوقف والابتداء في سورة يس والاستفادة منهما في تعليم اللغة العربية - Sugeng Warisman (Rayah Al-Islam, 2018)
The purpose of this study is to find out the knowledge of Al-Waqaf and Al-Ibtida' on the letter of Yaasin, and applying it to the teaching of Arabic.The method of completing this study is based on a scientific approach, namely: descriptive analytical method. Then Al-Waqaf and Al-Ibtida' are divided into four parts: taam, kaafin, hasan, and qabiih. And taam is a sentence not related to the sentence after or before in terms of meaning and words, and if the connection is in terms of meaning without words then it is referred to as kaafin, then if the connection is in terms of meaning and words but the meaning of the sentence does not change then it is called hasan , then if the relevance in terms of meaning and words then changes the meaning of the sentence then it is called qabiih. Then the knowledge of Al-Waqaf and Al-Ibtida' can also be implemented in the teaching of Arabic, which can be implemented through dialog formulations or texts or some examples of exercises.